Film Violence : History, Ideology, Genre. - Kendrick, Jim (Columbia University Press, 2010)
A concise and accessible introduction to the role violence has played in the cinema from the silent era to the present, this volume illustrates the breadth and depth of screen bloodshed in historical, cultural and industrial contexts. After considering problems of definition, this study offers a systematic history of film violence and examines three of the most popular violent genres (western, horror and action). It concludes with a case study on the centrality of film violence to the directors of the New American Cinema, such as Francis Ford Coppola, Martin Scorsese and Steven Spielberg, which offers a strong example of how violence, history, ideology and genre are all deeply intertwined.